Antiangiogenic Activity and Cytotoxicity of Triterpenoids and Homoisoflavonoids from Massonia pustulata and Massonia bifolia - Schwikkard, Sianne L.; Whitmore, Hannah; Corson, Timothy W.; Sishtla, Kamakshi; Langat, Moses K.; Carew, Mark; Mulholland, Dulcie A. (Planta Medica, 2018)
The Hyacinthaceae family (sensu APGII), with approximately 900 species in around 70 genera, plays a significant role in traditional medicine in Africa as well as across Europe and the Middle and Far East. The dichloromethane extract of the bulbs of Massonia pustulata (Hyacinthaceae sensu APGII) yielded two known homoisoflavonoids, (R)-5-hydroxy-3-(4-hydroxybenzyl)-7-methoxy-4-chromanone 1 and 5-hydroxy-3-(4-hydroxybenzyl)-7-methoxy-4-chromone 2 and four spirocyclic nortriterpenoids, eucosterol 3, 28-hydroxyeucosterol 4 and two previously unreported triterpenoid derivatives, (17S,23S)-17α,23-epoxy-3β,22β,29-trihydroxylanost-8-en-27,23-olide 5, and (17S, 23S)-17α,23-epoxy-28,29-dihydroxylanost-8-en-3-on-27,23-olide 6. Compounds 1, 2, 3, and 5 were assessed for cytotoxicity against CaCo-2 cells using a neutral red uptake assay. Compounds 1, 2, and 5 reduced cell viability by 70% at concentrations of 30, 100, and 100 µM, respectively. Massonia bifolia yielded three known homoisoflavonoids, (R)-(4′-hydroxy)-5-hydroxy-7-methoxy-4-chromanone 1, (R)-(4′-hydroxy)-5,7-dihydroxy-4-chromanone 7 and (R)-(3′-hydroxy-4′-methoxy)-5,7-dihydroxy-4-chromanone 9, two previously unreported homoisoflavonoids, (E)-3-benzylidene-(3′,4′-dihydroxy)-5-hydroxy-7-methoxy-4-chromanone 8 and (R)-(3′,4′-dihydroxy)-5-hydroxy-7-methoxy-4-chromanone 10, and a spirocyclic nortriterpenoid, 15-deoxoeucosterol 11. Compounds 1, 1Ac, 7, 8, 9, and 10 were screened for antiangiogenic activity against human retinal microvascular endothelial cells. Some compounds showed dose-dependent antiproliferative activity and blocked endothelial tube formation, suggestive of antiangiogenic activity.
Keywords: Massonia species; Hyacinthaceae; homoisoflavonoids; spirocyclic nortriterpenoids; cytotoxicity; angiogenesis